2006
DOI: 10.1007/s10552-005-0424-1
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1 and GSTT1 Polymorphisms, Cigarette Smoking, and Risk of Colon Cancer: A Population-based Case-control Study in North Carolina (United States)

Abstract: Cigarette smoke is a risk factor for colon cancer, but the importance of dose and interaction with genetic susceptibility remain poorly understood. We used data from a population-based case control study, to examine the association between cigarette smoking and colon cancer in African Americans and whites, and colon cancer and polymorphisms in GSTM1 and GSTT1. A total of 554 cases of primary colon cancer and 874 controls were included in this analysis. We found no association between cigarette smoking (ever ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 49 publications
2
28
0
1
Order By: Relevance
“…Furthermore, GSTM1 null genotype carriers are at a greater risk of developing colorectal malignancies. The results of this study are in agreement with those of numerous studies that have reported a significant effect of the GSTM1 null genotype on susceptibility to colorectal cancer (Sachse et al, 2002;Huang et al, 2006;Csejtei et al, 2008;Hlavata et al, 2010;Cai et al, 2014;Teng et al, 2014). The incidence of the null genotype in the current study was higher than that in similar studies that reported significant results (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, GSTM1 null genotype carriers are at a greater risk of developing colorectal malignancies. The results of this study are in agreement with those of numerous studies that have reported a significant effect of the GSTM1 null genotype on susceptibility to colorectal cancer (Sachse et al, 2002;Huang et al, 2006;Csejtei et al, 2008;Hlavata et al, 2010;Cai et al, 2014;Teng et al, 2014). The incidence of the null genotype in the current study was higher than that in similar studies that reported significant results (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…Cigarette smoking was found to be positively associated with colorectal cancer risk in the white but not in the black population [59] . This study also examined the possible association between GSTM1 and GSTT1 polymorphisms with colon cancer.…”
Section: Racial Polymorphism Variationmentioning
confidence: 90%
“…Environmental risk factors may be related to the formation of carcinogenic compounds such as polycyclic aromatic hydrocarbons (PAHs), heterocyclic amines and other mutagens during the preparation of food at high temperatures (Sinha et al, 1999;Schut and Snyderwine, 1999). Tobacco smoke is another risk factor (Huang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%